Bioresorbable electrospun mats of poly(D, L)-lactide/poly[(R, S)-3-hydroxybutyrate] blends for potential use in the treatment of difficult-to-heal skin wounds. (15th March 2021) - Zięba, Magdalena; Włodarczyk, Jakub; Gupta, Abhishek; Pastusiak, Małgorzata; Chaber, Paweł; Janeczek, Henryk; Musioł, Marta; Sikorska, Wanda; Kaczmarczyk, Bożena; Radecka, Izabela; Kowalczuk, Marek; Savickas, Arunas; et al.
Graphical abstract: Highlights: Mechanical properties of P(D, L)LA/a-PHB blends favour their medical applications. The Tg value of P(D, L)LA/a-PHB [70/30] blend loaded with PCAN is related to human body temperature. Hydrolysis of P(D, L)LA/a-PHB blend leads to non-toxic products that can be metabolized by the body. MTT ( in vitro ) tests support the potential use of P(D, L)LA/a-PHB electrospun mats in wound treatment. The biodegradable, non-toxic to human cells, P(D, L)LA/a-PHB elastic dressings were developed. Abstract: This study describes the preparation, physicochemical characterization and the biological studies of the polymeric delivery systems of proanthocyanidins (PCAN) extracted from Pelargonium sidoides for the potential use as wound dressings. In this study 20 wt% PCAN demonstrated good antimicrobial activity against Staphylococcus aures, a gram-positive wound pathogen. Poly(D, L-lactide) and atactic poly[(R, S)-3-hydroxybutyrate] biopolymers were used to construct biodegradable dressings. A series of polylactide/poly[(R, S)-3-hydroxybutyrate] (P(D, L)LA/a-PHB) blends, containing 10, 20, and 30 wt% of a-PHB were prepared and characterized by means of NMR, GPC, FT-IR, and DSC. Based on the findings, the P(D, L)LA/a-PHB [70/30 wt%] blend with the best thermomechanical properties (Tg value equal 37 °C) was chosen for the preparation of two kinds of electrospun mats, both with and without PCAN. About 50% of PCAN was released from the tested mats during the first 10–12 days of incubation. The electrospun mats with elastic properties, ensuring compatibility with the wound topology, were obtained. The studies of hydrolytic degradation of the constructed mats allowed us to gain complete knowledge of their hydrolysis process, and examine the PCAN release profile as well as identify and characterize the molecular structure of the degradation products of the developed delivery system. Furthermore, preliminary cytotoxicity MTT tests ( in vitro ) results support the potential application of PCAN-loaded (P(D, L)LA/a-PHB) electrospun mats in wound dressings.